Supply chain collaboration and integration enhance the response of fast-moving consumer goods manufacturers and retailers to customer's requirements - Ken Mathu; Selepe Phetla (South African Journal of Business Management, 2018)
Supply chain management has a critical role in steering business success through coordinated activities of the value chain partners. The success of fast-moving consumer goods companies (FMCGs) has a direct relationship with the performance of the leading retailers, which are their main channel of distribution. The supply chain of the leading South African food FMCGs and the corresponding retail chain stores was studied with the aim of establishing that collaboration and integration enhanced the response to the customers' requirements. The study was grounded on collaboration and integration theory, and a qualitative research methodology was used. Non-probability sampling was used, and senior managers selected from the two types of firms were interviewed. The data collected was transcribed, coded and thematically interpreted using content analysis. The outcome of the study indicated that supply chain collaboration and integration of the FMCG retailers, enhanced response to the customers' requirements.
Keywords: 650